Dynamics of Zooplankton in Relation to Physico-chemical Factors - Dar, I.A.; Rather, H.A.; Dar, M.A. (Our Nature, 2010)
The present investigation deals with limno- biotic status of the Bhoj wetland from January to August, 2009. From the data it was apparent that correlations between the physico-chemical factors and dynamics of zooplankton could be seen. Systematic sampling was done and five sampling stations were selected. The main objective of this research was to evaluate the correlation of zooplankton diversity with the physico-chemical factors. The analysis of data showed a positive correlation of copepods with temperature, indicating that the copepods develop better in warm periods after a mild and dump winter. While rotifers showed a negative correlation with temperature and a positive correlation with pH- value. Key words: Zooplankton, Physico-chemical parameters, Rotifera, Correlation DOI: 10.3126/on.v7i1.2567 Our Nature (2009) 7:168-176